1999
DOI: 10.1002/(sici)1521-4141(199910)29:10<3285::aid-immu3285>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

CD1high B cells: a population of mixed origin

Abstract: A specialized subpopulation of T lymphocytes is reactive to the MHC class I-like molecule CD1d. It is not clear which cells are the major antigen-presenting cells in vivo in the activation of CD1-restricted immune responses. We have characterized a subset of B lymphocytes expressing six- to eightfold higher levels of CD1 than the bulk of B cells. The cells have a surface phenotype (CD21(high), CD23(low), IgM(high), IgD(low)) found previously to characterize B cells residing in the splenic marginal zones. CD1(h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…4C and D). This agreed with the preservation of MZ B cells previously reported in GF rodents 17, 18. In contrast, MZ B cells were markedly decreased in RF mice in both percentage and absolute number, suggesting that the innate‐like B‐cell deficiency in RF mice was not due to the lack of products from their resident microbiota.…”
Section: Resultssupporting
confidence: 91%
“…4C and D). This agreed with the preservation of MZ B cells previously reported in GF rodents 17, 18. In contrast, MZ B cells were markedly decreased in RF mice in both percentage and absolute number, suggesting that the innate‐like B‐cell deficiency in RF mice was not due to the lack of products from their resident microbiota.…”
Section: Resultssupporting
confidence: 91%
“…However, it has also been shown that memory B cells of T cell‐dependent immune responses home to the MZ, indicating that the MZ B cell population in mice and rats is of mixed origin and function 32. The finding that about 90% of murine and rat MZ B cells carry unmutated V genes, while the remaining 10% are somatically mutated, is in line with this view of a mixed population 33, 34. In humans, the proportions of mutated and unmutated MZ B cells are reversed, with about 90% mutated and 10% unmutated cells 8, 13, 14.…”
Section: Discussionmentioning
confidence: 66%
“…We have also observed a defect in MZ B cells in PLCγ2 –/– mice backcrossed onto a B10.BR background (data not shown). Since the size of the MZ B cell compartment varies considerably between mouse strains and with age 26, 27, we suggest that this may partly account for the discrepancy between the data from different laboratories. In addition, the levels and types of commensal microbial flora in the gut have been shown to influence the size of the MZ pool 28, and these doubtlessly vary between mouse facilities.…”
Section: Discussionmentioning
confidence: 87%